Synergistic remineralization of enamel white spot lesions using mesoporous bioactive glasses loaded with amorphous calcium phosphate - Ren, Juan; Rao, Jianping; Wang, He; He, Wenjing; Feng, Jinnan; Wei, Danni; Zhao, Bin; Wang, Xing; Bian, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
The purpose of this study was to create a new delivery system that can synergistically remineralize enamel white spot lesions (WSLs).The delivery system (PAA-ACP@aMBG) was prepared by using amino-functionalized mesoporous bioactive glass (aMBG) as the carrier loaded with polyacrylic-stabilized amorphous calcium phosphate (PAA-ACP). The materials were characterized by transmission electron microscopy (TEM), X-ray powder diffraction (XRD), inductively coupled plasma‒optical emission spectrometry (ICP‒OES), and so on. Forty-eight artificial WSLs enamel samples were randomized to four groups: artificial saliva (negative control, NC), casein phosphopeptide-amorphous calcium phosphate (CPP-ACP), PAA-ACP@aMBG, and MBG. The effects of demineralization and remineralization of the enamel surface were compared by means of surface microhardness (SMH) measurements, surface color change measurements, fluorescence microscopy (FM), X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM).There was no significant difference in the surface microhardness recovery rate (SMHRR) or color recovery rate (CRR) among the CPP-ACP group, PAA-ACP@aMBG group and MBG group (P>0.05), but these values were significantly higher than those in the NC group (P<0.01). FM demonstrated that the remineralization depth in the PAA-ACP@aMBG group was significantly greater than that of the remaining three groups (P<0.01). SEM analysis indicated that the enamel demineralization marks in the PAA-ACP@aMBG group, CPP-ACP group, and MBG group were obscured by mineral deposition. PAA-ACP@aMBG showed good mineralization properties, implying its great potential for clinical application.